1995
DOI: 10.1074/jbc.270.44.26382
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Structural, and Transglutaminase Substrate Properties Of Human Loricrin, the Major Epidermal Cornified Cell Envelope Protein

Abstract: Loricrin is the major protein of the cornified cell envelope of terminally differentiated epidermal keratinocytes which functions as a physical barrier. In order to understand its properties and role in cornified cell envelope, we have expressed human loricrin from a fulllength cDNA clone in bacteria and purified it to homogeneity. We have also isolated loricrin from newborn mouse epidermis. By circular dichroism and fluorescence spectroscopy, the in vivo mouse and bacterially expressed human loricrins possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 37 publications
5
141
2
Order By: Relevance
“…The data show that there are no significant differences in the kinetic efficiencies between the three TGases. This observation is in marked contrast to previous data for recombinant SPR1, 16 trichohyalin 15 and loricrin 14 (Table 1), where the TGase 3 enzyme was the most efficient. On the other hand, the kinetic efficiency values for the three enzymes with SPR3 are two-to eightfold higher than The bar marks the position of the 67 kDa form of the enzymes; the asterisk marks the full-length enzyme.…”
Section: Kinetics Of Cross-linking Of Recombinant Spr3 By Tgases 1 2contrasting
confidence: 56%
See 1 more Smart Citation
“…The data show that there are no significant differences in the kinetic efficiencies between the three TGases. This observation is in marked contrast to previous data for recombinant SPR1, 16 trichohyalin 15 and loricrin 14 (Table 1), where the TGase 3 enzyme was the most efficient. On the other hand, the kinetic efficiency values for the three enzymes with SPR3 are two-to eightfold higher than The bar marks the position of the 67 kDa form of the enzymes; the asterisk marks the full-length enzyme.…”
Section: Kinetics Of Cross-linking Of Recombinant Spr3 By Tgases 1 2contrasting
confidence: 56%
“…A similar observation has been made previously in the in vitro cross-linking of loricrin. 14 The most likely explanation for this is that the enzymes inserted extensive intrachain cross-links. However, this observation makes little biological sense, as the available data shows that the SPR3 protein forms extensive interchain linkages instead 10 in its proposed cross-bridging role in CE structures.…”
Section: Isolation Of Native Mouse Spr3 Proteinmentioning
confidence: 99%
“…Seven members of the TGase family have been identified in the human genome so far, which are listed in Table 1. Four of these, TGases 1, 2, 3 and ✕ are commonly expressed in epithelia such as the epidermis (Kim et al , 1991;Aeschlimann et al, 1998), although to date only TGases 1 and 3 have proven importance in CE assembly (Candi et al, 1995;Tarcsa et al, 1997;Tarcsa et al, 1998Candi et al, 1999. It has also been proposed that the cross-linking by these enzymes coordinates mechanically the association between the CE and the underlying intracellular keratin intermediate filaments , and perhaps also in the bundling of keratin filaments (Clement et al, 1998).…”
Section: The Tgasesmentioning
confidence: 99%
“…Loricrin contains three glycine rich domains which are thought to form uniquely flexible glycine loops (Steinert et al, 1991), interspersed by glutamine-rich motifs and flanked by lysine-and glutamine-rich amino and carboxy terminal domains (Mehrel et al, 1990;Hohl et al, 1991a). In vitro cross-linking experiments using recombinant human loricrin have demonstrated that the TGase 1 and 3 enzymes utilize different glutamine and lysine residues, implying that both enzymes have distinctly complementary and essential functions in the utilization of loricrin for CE assembly in vivo (Candi et al, 1995).…”
Section: Structural Protein Components Of Cesmentioning
confidence: 99%
“…Loricrin (LOR) and involucrin (IVL) are important proteins that facilitate terminal differentiation of the epidermis and formation of the skin barrier [7][8][9][10][11][12]. Human LOR is an insoluble protein initially expressed in the granular layer of the epidermis during cornification, and comprises 80% of the total protein mass of the cornified envelope (CE) [7,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%